Pengembangan Kompetensi Kritis Melalui Model Problem Based Learning Terhadap Kemampuan Belajar Siswa di Sekolah Dasar - Inas Salsabila; Siti Masyithoh (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Critical competence plays an important role in students' ability to solve a problem that occurs. Through PBL, students are trained to develop ideas, or ideas that can facilitate them in problem solving and learning activities at school. By using the Problem-Based Learning paradigm to achieve learning objectives in elementary schools, students' critical competencies are developed. This form of learning looks at the relationship between critical thinking and student learning outcomes by using a qualitative approach with literature study as a source of in-depth analysis. A suitable approach to help students build critical thinking skills is a problem-based learning strategy. Students are encouraged to actively participate in solving problems that arise when using the Problem-Based Learning paradigm, according to the learning outcomes. By using this problem-based learning approach, students are encouraged to investigate a problem in more detail and from a broader perspective. Students can come up with original ideas in this situation or ideas for problem solving. By developing students' critical thinking skills and highlighting the important role that teachers play in fostering an enjoyable learning environment and acting as facilitators in the teaching and learning process, the Problem Based Learning model has been proven to improve the quality of teaching and student learning outcomes in educational settings.